Neutrophil‐derived advanced glycation end products‐Nε‐(carboxymethyl) lysine promotes RIP3‐mediated myocardial necroptosis via RAGE and exacerbates myocardial ischemia/reperfusion injury. Issue 12 (30th October 2019) - Yang, Ji'e; Zhang, Feng; Shi, Huairui; Gao, Yang; Dong, Zhen; Ma, Leilei; Sun, Xiaolei; Li, Xiao; Chang, Suchi; Wang, Zeng; Qu, Yanan; Li, Hua; et al.
Abstract : Nε‐(carboxymethyl) lysine (CML), the major member of advanced glycation end products, was widely studied in diabetic complications and aging‐associated diseases. However, the impact of CML on myocardial ischemia/reperfusion injury (MI/RI) was rarely reported. In the present study, CML was increased in both patients with acute myocardial infarction (53.4 ± 7.8 vs. 28.1 ± 4.4 ng; P = 0.017), and mice underwent MI/RI (16.4 61.4 vs. 10.8 ± 0.9 ng; P = 0.006). Depletion of neutrophils reduced CML (17.8 ± 1.0 vs. 9.9 ± 0.3 ng; P < 0.001), indicating neutrophils were the major cells contributing to CML formation during MI/RI. CML treatment exacerbated MI/RI by elevating myocardial injury marker (274.3 ± 18.0 vs. 477.2 ± 34.3 pg P < 0.001), enlarging myocardial infarct size (32.9 ± 3.6 vs. 45.2 ± 3.8%; P = 0.03), increasing myocardial fibrosis (17.5 ± 1.6 vs. 29.7 ± 2.2%; P < 0.001) and impairing cardiac function (59.4 ± 2.4% vs. 46.0 ± 1.3%; P = 0.001). Further study revealed that CML increased the phosphorylation of receptor interacting protein (RIP) 3, an important initiator of necroptosis, and its downstream proteins. Receptor for advanced glycation end product (RAGE) deficiency effectively blocked RIP3 phosphorylation induced by CML and rescued CML‐mediated MI/RI, indicating CML promoted RIP3‐mediated necroptosis through RAGE. In addition, glyoxalase‐1 overexpression could effectively attenuate MI/RI by reducing CML formation, providing a potential therapeutic target for MI/RI.—Yang, J., Zhang, F., Shi, H., Gao, Y., Dong, Z., Ma, L., Sun, X., Li, X., Chang, S., Wang, Z., Qu, Y., Li, H., Hu, K., Sun, A., Ge, J. Neutrophil‐derived advanced glycation end products‐Nε‐(carboxymethyl) lysine promotes RIP3‐mediated myocardial necroptosis via RAGE and exacerbates myocardial ischemia/reperfusion injury. FASEB J. 33, 14410‐14422 (2019). www.fasebj.org